Penerapan Media Quizizz pada Pembelajaran Teks Hikayat Kelas X - Febrianto, Hermawan Ardi; Asrofah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of this research is to determine the application of quizizz media in learning saga texts for class 10 students at SMAN 11 Semarang. This article presents an innovative approach that combines technology with traditional curriculum materials. In this context, this article discusses how quizizz integration can increase student engagement, strengthen conceptual understanding, and advance their critical skills. With a focus on interactivity, instant feedback, and measurability of individual progress, this approach not only provides an engaging learning experience, but also allows teachers to optimize the learning process according to each student's needs and abilities. The main problem is students' low interest and understanding of the saga text material. The research method involves implementing quizizz as an interactive tool in learning, with a focus on online quizzes that support understanding of saga texts. The findings show an increase in students' interest and understanding of saga texts through the use of quizizz.